Profiling the promotion of green technology in industry through GTFS - Adebiyi, Opeyemi Olajide; Mohamad, Norhidayah; Ahmad Murad, Murzidah; Md Isa, Mohamed Hafiz; Cruz, M. D. (J Fundam Appl Sci., 2018)
Malaysia has devoted itself into promoting a green economy by creating some programs that would foster the partnership of green technology and green financing. This has given birth to the Green Technology Financial Scheme, which was started in 2010 supporting companies that are advocating green technology. It covers 2 types of companies and 4 sectors of green technology that any company can choose from. Since its initiation, hundreds of companies have been recipients of the scheme. The paper studied the Green Technology Financial Scheme’s overall profile, starting from the rationale of why it was formed, to the statistics of its recipients. This study is important indicator to encourage other industries to adopt green technology as their competitive advantage for extensive competition. An analysis is made as to how balanced is the distribution of financing among the sectors that has been identified.